Current trends in paediatric and neonatal ventilatory care – a nationwide survey. (24th September 2012) - Ålander, Merja; Peltoniemi, Outi; Saarela, Timo; Anttila, Eija; Pokka, Tytti; Kontiokari, Tero
Abstract Aim: To assess daily practices in paediatric and neonatal ventilatory care in Finland. Methods: All neonatal and paediatric intensive care units in Finland were sent a questionnaire on ventilatory strategies and were offered a 3‐month prospective survey. Results: A total of 96% of units returned the questionnaire, and clinicians agreed on most of the principles of lung‐protective ventilation. Seventeen hospitals (94%) joined the prospective survey. On average, 2.3 new ventilation episodes were started daily, and totally 211 episodes were monitored. Pulmonary problems (64%) were the main cause of treatment in neonates and postoperative care (68%) in older children. Synchronized intermittent mandatory ventilation with pressure support was the primary mode in 42% of episodes. Hypocapnia was observed repeatedly in all units. In adult intensive care units, children often received high oxygen fraction, leading to hyperoxia, and they were frequently sedated with propofol, which is not licensed for that purpose. A large proportion of children had only light sedation or no sedation at all. Despite the different strategies and practices, most episodes resulted in a favourable outcome. Conclusion: Most of the principles of lung‐protective ventilation have been well accepted by clinicians. More attention should be paid to achieving normocapnia and normoxia and to the correct use of sedatives, especially in units that only occasionally provide paediatric ventilation.